2015
DOI: 10.1128/mcb.00764-15
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation-Induced Interactions between Protease-Activated Receptor 1 and Proprotein Convertases in HIV-Associated Neurocognitive Disorder

Abstract: eThe proprotein convertases (PCs) furin, PC5, PACE4, and PC7 cleave secretory proteins after basic residues, including the HIV envelope glycoprotein (gp160) and Vpr. We evaluated the abundance of PC mRNAs in postmortem brains of individuals exhibiting HIV-associated neurocognitive disorder (HAND), likely driven by neuroinflammation and neurotoxic HIV proteins (e.g., envelope and Vpr). Concomitant with increased inflammation-related gene expression (interleukin-1␤ [IL-1␤]), the mRNA levels of the above PCs are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
54
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 57 publications
4
54
0
Order By: Relevance
“…CHO cells were transfected to express the dual tagged PAR‐1 using the same protocol used to generate EGFRvIII. The plasmid construct of the human protease activated‐receptor one with fluorescent tags was provided as a generous gift from Dr Nabil Seidah (Clinical Research Institute of Montreal, University of Montreal, Quebec, Canada) . TF silencing was carried out using lentiviral particles carrying a human TF‐ specific shRNA sequence and as described in …”
Section: Methodsmentioning
confidence: 99%
“…CHO cells were transfected to express the dual tagged PAR‐1 using the same protocol used to generate EGFRvIII. The plasmid construct of the human protease activated‐receptor one with fluorescent tags was provided as a generous gift from Dr Nabil Seidah (Clinical Research Institute of Montreal, University of Montreal, Quebec, Canada) . TF silencing was carried out using lentiviral particles carrying a human TF‐ specific shRNA sequence and as described in …”
Section: Methodsmentioning
confidence: 99%
“…Indeed, it was recently shown that in an effort to limit viral infections, host cells that are infected by a number of viruses provoke an interferon response to inhibit the enzymatic activity of furin-like enzymes. It was also demonstrated that HIV infection induces the expression of either the protease activated receptor 1 (PAR1) (Kim et al, 2015) or guanylate binding proteins 2 and 5 (GBP2,5) (Braun and Sauter, 2019) that restrict the trafficking of furin to the trans Golgi network (PAR1) or to early Golgi compartments (GBP2,5) where the proprotein convertase remains inactive. Altogether, these observations suggest that inhibitors of furin-like enzymes may contribute to inhibiting virus propagation.…”
Section: Tablementioning
confidence: 99%
“…Actually, it has been recently demonstrated that HCs infected by several kinds of viruses stimulate an interferon-based activity to block the enzymatic activity of furin-like enzymes (Lodermeyer et al, 2013). It was also revealed that virus infection triggers the upregulation of some receptors (Braun & Sauter, 2019;Kim et al, 2015) that inhibit the furin trafficking in post-Golgi compartments.…”
Section: Enzyme Inhibitors As Therapeutic Platformsmentioning
confidence: 99%